Registration of immigrants’ educational attainment in Sweden: an analysis of sources and time to registration - Samaneh Khaef (Genus, 2022)
Abstract Swedish register data include a number of variables related to individuals’ educational level. In contrast to many other countries, the registers even include information on the education obtained by immigrants outside Sweden. For studies on immigrants’ labour market integration, this is an important asset. However, the quality of data in terms of the source and extent of data coverage for different migrant groups is less well-known. This explorative paper investigates the sources of information for immigrants’ educational levels, and examines the time taken until their education is registered for different migrant groups. Employing register data on immigrants who arrived in Sweden in the period 2000–2016, the methods include a descriptive analysis of the main sources of educational attainment, and event history analysis to estimate survival rates for not being in the educational registers. The results indicate that the ‘survey of foreign-born’ and the Swedish Public Employment Service are the two major sources of information regarding immigrants’ educational attainment in their year of arrival. However, the survey’s non-response rate is high. Results from the event history analysis show that as the length of stay in the country increases, the share of immigrants with missing educational information decreases substantially, especially after 2 years, with rather large differences for groups of immigrants. For the majority of refugees and family migrants, 2 years after arrival their educational levels are registered, while the educational levels of many Nordic migrants remained unregistered even after 10 years. In addition, attained education of women and younger immigrants is more often registered. Measuring the educational level of refugees and family migrants from 2 years after arrival can provide a reasonable representation of their educational characteristics at the time of migration, while it is questionable to use Nordic migrants’ educational level at any time.